Effects of Unburned Lime on Soil pH and Base Cations in Acidic Soil. (26th November 2013) - Nduwumuremyi, Athanase; Ruganzu, Vicky; Mugwe, Jayne Njeri; Cyamweshi Rusanganwa, Athanase
Abstract : Sustainable agriculture is threatened by the widespread soil acidity in many arable lands of Rwanda. The aim of this study was to determine the quality of unburned limes and their effects on soil acidity and base cations in acidic soils of high land of Buberuka. The lime materials used were agricultural burned lime and three unburned lime materials, Karongi, Musanze, and Rusizi. The test crop was Irish Potato. All lime materials were analyzed for Calcium Carbonate Equivalent (CCE) and Fineness. A field trial in Randomized Complete Block Design was established in 2011 at Rwerere research station. The treatments comprised of the four lime materials applied at four levels: 0, 1.4, 2.8, and 4.3 t ha −1 of CCE. Soil cations (Ca 2+, Mg 2+, K +, and Na + ) were determined by extraction method using atomic absorption spectrophotometer for Ca and Mg and flame photometer for K and Na. The Al 3+ was determined using potassium chloride extraction method. Experimental soil baseline showed that the soil was very strongly acidic (2.8 cmol kg −1 Al 3+ ). The unburned limes were significantly (P < 0.001 ) different in terms of CCE and fineness. A higher CCE was recorded in agricultural burned and Rusizi unburned limes (86.36% and 85.46%, resp.). In terms of fineness, agricultural burned and Musanze unburned lime were higher (70.57 and 63.03%, resp.). Soil acidity significantly affected from 4.8 to 5.6 pH and exchangeable Al reduced from 2.8 cmol kg −1 to 0.16 cmol kg −1 of Al 3+ . Similarly all cations affected by unburned limes application, significantly (P < 0.001 ) Ca saturation increased from 27.44 to 71.81%, Mg saturation from 11.18 to 36.87% and significantly (P < 0.001 ) Al saturation reduced from 58.45 to 3.89%. The increase of Mg saturation was observed only with Karongi unburned lime application. This study recommends therefore, the use of 2.8 t ha −1 of CaCO3 of Rusizi or Musanze unburned lime as alternative to the agricultural burned lime for improving soil acidity and base cations in acidic soils.